Digital Transformation in Primary Health Care: Evaluation of Information Technology Adoption and Management Practices - Riyantori, Refki; Buka , Sisilia Prima Yanuaria (Smart International Management Journal, 2025)
Primary Health Care (PHC) serves as the frontline of national health systems, making digital transformation essential for improving service quality, efficiency, and coverage. This study aims to assess the level of Information Technology (IT) adoption and evaluate supporting management practices at Pusat Kesehatan Masyarakat (Puskesmas) in Indonesia. A descriptive quantitative approach was employed using official secondary data obtained from government institutions, including the Ministry of Health, BPJS Kesehatan, and the Central Statistics Agency, with West Java Province designated as the study area. The analysis encompassed five dimensions: infrastructure availability, utilization of clinical information systems (SIMPUS/ASIK), IT human resource capacity, service performance indicators, and IT management maturity. The results indicate a high adoption rate of basic infrastructure such as internet access and computers; however, the utilization of core clinical systems, including ASIK and PCare, varies considerably across Puskesmas. Limited availability of dedicated IT personnel and insufficient IT management training for leadership were identified as key constraints. Overall, successful digital transformation in PHC depends not only on adequate infrastructure but also on strengthened management practices, particularly in human resource capacity, data governance, and effective use of clinical information systems to achieve improved service outcomes.